2017
DOI: 10.3389/fpls.2017.01684
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Calmodulin Are Involved in Nitric Oxide-Induced Adventitious Rooting of Cucumber under Simulated Osmotic Stress

Abstract: Osmotic stress is a major form of abiotic stress that adversely affects growth and development of plants and subsequently reduces yield and quality of crops. In this study, the effect of nitric oxide (NO) and calcium (Ca2+) on the process of adventitious rooting in cucumber (Cucumis sativus L.) under simulated osmotic stress was investigated. The results revealed that the effect of exogenous NO and Ca2+ in promoting the development of adventitious roots in cucumber seedlings under simulated osmotic stress was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 81 publications
4
44
0
Order By: Relevance
“…Our results further show that Ca 2+ /CaM might be involved in the NO-regulated postharvest freshness process of cut lily flowers. The earlier reports about other plants, including cucumber ( Niu et al, 2017 ), fava bean ( Zhao et al, 2013 ), grape ( Vandelle et al, 2006 ), tobacco ( Lamotte et al, 2006 ), Arabidopsis ( Abdul-Awal et al, 2016 ), tall fescue ( Xu et al, 2016 ), tomato ( Siddiqui et al, 2017 ), wheat ( Tian et al, 2015 ), rice ( Chen and Kao, 2012 ), and marigold ( Liao et al, 2012b ), are in conformity with our results, suggesting there are intricate interplays between NO and Ca 2+ .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results further show that Ca 2+ /CaM might be involved in the NO-regulated postharvest freshness process of cut lily flowers. The earlier reports about other plants, including cucumber ( Niu et al, 2017 ), fava bean ( Zhao et al, 2013 ), grape ( Vandelle et al, 2006 ), tobacco ( Lamotte et al, 2006 ), Arabidopsis ( Abdul-Awal et al, 2016 ), tall fescue ( Xu et al, 2016 ), tomato ( Siddiqui et al, 2017 ), wheat ( Tian et al, 2015 ), rice ( Chen and Kao, 2012 ), and marigold ( Liao et al, 2012b ), are in conformity with our results, suggesting there are intricate interplays between NO and Ca 2+ .…”
Section: Discussionsupporting
confidence: 92%
“…The results indicate that Ca 2+ was involved in the NO-related postharvest freshness, and the positive effect of NO might depend on increased Ca 2+ content ( Figure 6 ), at least partly. Recent studies from our laboratory have shown that intracellular Ca 2+ amount was increased by NO in cucumber hypocotyls during the development of adventitious roots under osmotic stress ( Niu et al, 2017 ). These results are in full agreement with the findings of Siddiqui et al (2017) , who found that exogenous NO and Ca 2+ applied individually as well as in combination significantly enhanced of Ca 2+ content under both heat stress and non-stress conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitric oxide (NO) has also been shown to be involved in AR formation in many species [ 65 , 66 , 67 ]. Based on a previous study in cucumber explants, proteins extracted form plants with NO-donor sodium nitroprusside (SNP) and IAA-treatment showed an activity of protein kinase, which could be inhibited by mitogen-activated protein kinases (MAPKs) inhibitor.…”
Section: Discussionmentioning
confidence: 99%